BRIEF OVERVIEW OF THE TOY DEVELOPMENT IN PREHYSTORY AND ANTIQUITY - POLCIC, Ludovit (Trends in education, 2009)
The article covers a brief historical development of toy in prehistory and antiquity.
Keywords: toy; child; material; shape; culture; habits; education.